Study of the combustion characteristics of sewage sludge pyrolysis oil, heavy fuel oil, and their blends. (15th June 2020) - Kuan, Yong-Hao; Wu, Fang-Hsien; Chen, Guan-Bang; Lin, Hsien-Tsung; Lin, Ta-Hui
Abstract: An investigation was performed to determine the heating characteristics of sludge pyrolysis oil (SPO), heavy fuel oil (HFO), and their blends. The ignition temperature, burnout temperature, flammability index ( C ), and combustion characteristics index ( S ) of various fuels were evaluated using a thermogravimetric analysis (TGA). Furthermore, the heating behavior of the SPO, HFO droplets, and their blends was also investigated using a suspended droplet experimental system. The TGA results showed that the combustion process had three stages. In the volatile decomposition and burning stage, the fuel blends with a higher SPO content exhibited higher flammability and combustion characteristics indexes due to the release and oxidation of the lightweight components. However, there were less differences in the flammability and combustion characteristics indexes for the high weight components that burned out in the final stage. Distinct stages could be observed in the suspended droplet experiments. Different vaporization/combustion rates for different fuels were also evaluated, and the results showed that adding SPO to HFO significantly improved combustion performance. A constant combustion rate was obtained with the addition of SPO to HFO. A higher SPO content in the fuel blend increased the frequency and magnitude of the micro-explosion and reduced residual products. Highlights: Combustion behaviors of sludge pyrolysis oil and heavy fuel oil were studied. Sludge pyrolysis oil improves the fluidity and enhances combustion performance. Sludge pyrolysis oil enhances combustion performance for volatile components. The droplet vaporization/combustion rates of blended fuels were evaluated. Sludge pyrolysis oil increased the frequency and magnitude of the micro-explosion.